Isoterm Dan Termodinamika Adsorpsi Pada Methylene Blue Menggunakan Hidroksiapatit - Dian Novita Rahmawaty; Yelmida Azis; Cory Dian Alfarisi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The adsorption model was carried out to find out the appropriate adsorption mechanism in the methylene blue adsorption process using hydroxyapatite. The aim of this study was todetermine the equilibrium time, the effects of methylene blue’s initial concentration, adsorption temperatures and the adsorption models. Analysis was conducted by spectrophotometric method, then tested on the Langmuir, Freundlich, Temkin and Dubinin-Radushkevich (DRK) isotherm model. The result showed that the best initial concentration of methylene blue for adsorption temperature 30℃ with adsorption capacity 2,090 mg/g and 41,79% of removal efficiency. The adsorption followed the Freundlich isotherm model. Thethermodynamic parameters (ΔH = -8,4 kJ/mol, ΔG < 0 dan ΔS = -80,70 J/mol K) indicated that he adsorption process was a physically and spontaneously excothermic reaction.Keywords: adsorption, Freundlich, hydroxyapatite, isotherm, methylene blue.